HOW THE PAST SHAPES CURRENT STORIES: (EPI)GENETIC EPIDEMIOLOGICAL PROFILES OF METABOLIC SYNDROME IN BRAZILIAN MENNONITES - Ana Luiza Sprotte Mira; Kathleen Lietke Kolb; Larissa Schneider; Eduardo Delabio Auer; Priscila Ianzen dos Santos; Guilherme Luiz da Rocha; Valéria Bumiller Bini; Gabriela Canalli Kretzschmar; Sheila Coelho Soares Lima; Angelica Beate Winter Boldt (Arquivos do Mudi, 2023)
Mennonites present cc. 500 years genetic isolation and three bottleneck events that reduced their genetic diversity. In order to identify (epi)genetic markers for metabolic syndrome (MS), we used a modified version of the Brazilian National Health Survey to interview 762 Mennonites from three settlements, between 2016-2023. We compared 63 vs. 127 exomes (Illumina HiSeq) from Mennonites with/without metabolic syndrome (MS) and genotyped candidate variants in regulatory regions with mass spectrometry (iPLEX) and sequence-specific amplification (PCR-SSP). We also evaluated DNA methylation of the NR3C1 and FKBP5 genes in peripheral blood mononuclear cells (PBMCs) of up to 66 and 141 individuals with/without MS. MS prevalence was 35.8%, similar to Neobrazilians (34.8%), paradoxically followed by a three times lower prevalence of acute myocardial infarction (AMI). Among independent MS risk factors, we found lower maternal warmth in infancy (OR=1.59, P=0.019) and a higher susceptibility to AMI with the harshest migratory route to Brazil (OR=1.57, P=0.001). Thirty-nine variants of 34 genes were associated with MS (p<0.02), 41% create/disrupt CpG sites and 12 were associated with visceral adipose and/or cardiovascular tissue expression. There were no methylation differences between individuals with and without MS in PBMCs with the NR3C1 and FKBP5 genes, pointing to other epigenetic causal effects. In conclusion, Mennonites have a peculiar epidemiological profile marked by (epi)genetic founder effects that also affect their metabolism, calling for urgent action for prevention and to alleviate the burden of comorbidities due to late diagnosis.